2015
DOI: 10.1021/acscatal.5b00808
|View full text |Cite
|
Sign up to set email alerts
|

Impurity Ion Complexation Enhances Carbon Dioxide Reduction Catalysis

Abstract: Herein, we show that group 11 CO 2 reduction catalysts are rapidly poisoned by progressive deposition of trace metal ion impurities existent in high purity electrolytes. Metal impurity deposition was characterized by XPS and in situ stripping voltammetry and is coincident with loss of catalytic activity and selectivity for CO 2 reduction, favoring hydrogen evolution on poisoned surfaces. Metal deposition can be suppressed by complexing trace metal-ion impurities with ethylenediaminetetraacetic acid or solid su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
269
3
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 236 publications
(310 citation statements)
references
References 54 publications
(103 reference statements)
11
269
3
10
Order By: Relevance
“…Since CO 2 RR usually takes place at highly cathodic potentials, transition metal ions (such as Fe 3+ , Ni 2+ , Cu 2+ , and so on) in the electrolyte even at 5 ppm can be electrodeposited onto the working electrode during CO 2 RR and unexpectedly contaminate the working electrode . To remedy this problem, the electrolyte is usually pre‐electrolyzed to lower the concentration of transition metal ions or added with, for example, metal chelator ethylenediaminetetraacetic acid to block the deposition of these impurities onto the working electrode …”
Section: Fundamentals Of Electrochemical Co2 Reductionmentioning
confidence: 99%
“…Since CO 2 RR usually takes place at highly cathodic potentials, transition metal ions (such as Fe 3+ , Ni 2+ , Cu 2+ , and so on) in the electrolyte even at 5 ppm can be electrodeposited onto the working electrode during CO 2 RR and unexpectedly contaminate the working electrode . To remedy this problem, the electrolyte is usually pre‐electrolyzed to lower the concentration of transition metal ions or added with, for example, metal chelator ethylenediaminetetraacetic acid to block the deposition of these impurities onto the working electrode …”
Section: Fundamentals Of Electrochemical Co2 Reductionmentioning
confidence: 99%
“…The electrolyte was CO 2 -saturated 0.1 M NaHCO 3 (pH 6.75), which had been treated with an ion exchange resin (Chelex) to minimize the concentration of transition metal impurities 19,20 . Prior to polarization at the stated potential, the samples were subjected to a cathodic current of −2.0 mA cm…”
Section: Electrochemical Performancementioning
confidence: 99%
“…Numerous Earth-abundant catalysts have been developed for the OER, most of them consisting of transition metals such as Ni and Fe, which are prone to dissolve and redeposit on the CO 2 reducing cathode. This leads to poisoning of the electrode 19 , a problem that may be averted by avoiding the use of elements foreign to the cathode. We therefore decided to investigate OER electrodes that are made from the same elements as the cathode, leading to a bifunctional catalyst configuration that has the additional benefit of making the device simpler and more cost effective.…”
Section: Bifunctional Catalysismentioning
confidence: 99%
“…Consequently, it seems that predicting how hydrocarbons are formed at Cu‐based electrodes is more complicated than simply using CO heat of adsorption (Figure ). Indeed, hydrocarbon evolution studies have shown that even a tiny fraction of secondary metals can be catastrophic to the hydrocarbon evolution ability of a copper electrode . This factor makes the exploration of alloys for hydrocarbon evolution much more challenging.…”
Section: Co2→c2 With Electrocatalytic Alloysmentioning
confidence: 99%